Effects of addition of copper particles of different size to Sn-3.5Ag solder - Nadia, A.; Haseeb, A.S. Md. Abdul (Springer, 2012)
In this study, copper particles with different sizes 20-30 nm, 3 and 10 mu m were incorporated into Sn-3.5Ag solder paste to form Sn-Ag-Cu composite solder. The Cu particles were added at 0.7 and 3 by paste mixing for 30 min. The composite solder samples were prepared on copper substrate at 240A degrees C for 60 s. Differential scanning calorimetry was conducted to measure the melting point of the composite solder. The wetting angle and microstructure of the composite solder were studied using optical microscope and scanning electron microscope. Micro hardness was measured using a 10 gf load. It was reported that the lowest melting point was obtained at 216.3A degrees C when Cu nanoparticles was added at 3 to Sn-3.5Ag. The microstructure of Sn-3.5Ag solder structure was dendritic in nature. With the addition of Cu nanoparticles, the microstructures were modified with more refined Sn structures. The existence of sunflower morphology of un-melted copper was observed when Cu microparticles were added.